PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN DORATOON KELAS IV BAHASA INDONESIA Penelitian Research and Development Pada Peserta Didik Kelas IV di Sekolah Dasar Negeri Loji 2 Kota Bogor Semester Ganjil Tahun Pelajaran 2024/2025 - Nurul Fauziyatil Azimah; Nita Karmila; Dendy Saeful Zen (STKIP Subang, 2026)
Nurul Fauziyatil Azimah (037120065) This research is a research and development (RnD) with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation) which aims to determine the feasibility of animated video learning media using Doratoon. This research was conducted on fourth grade students of SDN Loji 2 in the 2024/2025 academic year. The three stages of testing carried out in this study are media experts, linguists, and material experts and the distribution of student response questionnaires to the implemented media. The results of the validation test by media experts obtained a percentage of 86% with decent criteria, language experts obtained a percentage of 100% with very feasible criteria, material experts I obtained a percentage of 100% with very feasible criteria and material experts II obtained a percentage of 88%. The results of the learner response questionnaire showed a percentage of 89.05% with a decent category. Thus it can be concluded that the animation video is feasible for students to use in the learning process of grade IV SD.